CORRECTION OF MESOZOIC STRATIGRAPHY IN NW CENTRAL AMERICA FROM THE ISTHMUS OF TEHUANTEPEC TO NICARAGUA - MULLERRIED, FEDERICO KG (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
Ten localities in the area are considered; not all known horizons are well established, especially in the U Cretaceous, but those of the U Jurassic, and L and M Cretaceous, are better indicated Types known for each locality are listed and some briefl
CIENC MEX
Keywords: CORRECTION, MESOZOIC STRATIGRAPHY, N W CENTRAL AMERICA, ISTHMUS OF TEHUANTEPEC, NICARAGUA; MULTIDISCIPLINARIA; PALEONTOLOGIA; PALEONTOLOGIA ANIMAL